The Influence of Teaching Tenses through Group Discussion Method towards Student's Achievement In Tenses Mastery - Ade Sudirman (Journal of English Education Studies, 2018)
This research aims to investigate the influence of teaching English tenses through group discussion method towards student’s achievement in tenses mastery at 1st semester students of English department of Mathla’ul Anwar University, Banten. In this research, writer employs the quantitative approach that based on the result of proposing item tests to respodents of the research. Meanwhile design with the characteristics of experimental method, here the researcher conducted test as an instrument. The research done through three steps: first, the writer selected students of Mathla’aul Anwar University as subjects, second, the writer taught tenses through group discussion method at experimental class, while control class taught by giving homework. The treatment is processed by a pretest, treatment, and ended by posttest. It is done to know which one is more effective towards students’ achievement in tenses matery. After that, the writer calculated and analysed the data. The last step is reporting the result. The result of posttest show us that the mean of experimental class is higher than at control class. The result of calculation of t-test shows that tcount (2,63) is higher than tcritic (1,67) in 5% level significant. These tell us that teaching tenses through group discussion method is effective to improve the students’ achievement in tenses matery. The research hypotheses is “there is significance influence of using group discussion method in teaching tenses towards students’ achievement in tenses matery”. From all the data above, the writer concludes that his hypotheses is justifiable.